Effect of internode length and blade angle of newly-formed tea shoots on machine-plucking performance of high quality tea - LUO Yao-ping; SONG Ting-ting; WEN Dong-hua; TANG Meng; CAI Wei-zhi (浙江大学学报. 农业与生命科学版)
Changes in the internode length and blade angle during development of new tea shoots were investigated using potted plants of cultivars Zhenong 113, Longjing 43, and Zhenong 139. The results reveal that the development of internode length of the three tested cultivars followed an S-type curve. The internode length of Zhenong 139 was the longest, and that of Longjing 43 the shortest, with Zhenong 113 in between. The optimum time for machine-plucking was on the 15th day after the stunted-leaf was opened, at which the internode length and blade angle were most suitable for machine-plucking operation and the broken shoots and leaves were the least. If machine-plucking was performed on the 12th day after the stunted-leaf was opened, the percentage of broken leaves was high because the internode length was about half of its mature shoots. Whereas, the shoots would be mature not to be used as materials for processing high quality tea on the 18th day after the stunted-leaf was opened. It was also found that high levels of fertilization would increase the internode length and was in favor of machine-plucking.